Investigation of Aerosol Types and Vertical Distributions Using Polarization Raman Lidar over Vipava Valley - Longlong Wang; Marija Bervida Mačak; Samo Stanič; Klemen Bergant; Asta Gregorič; Luka Drinovec; Griša Močnik; Zhenping Yin; Yang Yi; Detlef Müller; Xuan Wang (Remote Sensing, 2022)
Aerosol direct radiative forcing is strongly dependent on aerosol distributions and aerosol types. A detailed understanding of such information is still missing at the Alpine region, which currently undergoes amplified climate warming. Our goal was to study the vertical variability of aerosol types within and above the Vipava valley (45.87<semantics>°</semantics>N, 13.90<semantics>°</semantics>E, 125 m a.s.l.) to reveal the vertical impact of each particular aerosol type on this region, a representative complex terrain in the Alpine region which often suffers from air pollution in the wintertime. This investigation was performed using the entire dataset of a dual-wavelength polarization Raman lidar system, which covers 33 nights from September to December 2017. The lidar provides measurements from midnight to early morning (typically from 00:00 to 06:00 CET) to provide aerosol-type dependent properties, which include particle linear depolarization ratio, lidar ratio at 355 nm and the aerosol backscatter Ångström exponent between 355 nm and 1064 nm. These aerosol properties were compared with similar studies, and the aerosol types were identified by the measured aerosol optical properties. Primary anthropogenic aerosols within the valley are mainly emitted from two sources: individual domestic heating systems, which mostly use biomass fuel, and traffic emissions. Natural aerosols, such as mineral dust and sea salt, are mostly transported over large distances. A mixture of two or more aerosol types was generally found. The aerosol characterization and statistical properties of vertical aerosol distributions were performed up to 3 km.